Evaluation of continuous intravenous lidocaine on brain relaxation, intraoperative opioid consumption, and surgeon's satisfaction in adult patients undergoing craniotomy tumor surgery: A randomized controlled trial. Issue 36 (9th September 2022) - Chandra, Susilo; Pryambodho, Pry; Omega, Andy
Abstract : Background: In craniotomy tumor removal, brain relaxation after dura opening is essential. Lidocaine is known to have analgesic and antiinflammatory effects. It is excellent in decreasing cerebral metabolic rate of oxygen, cerebral blood flow, and cerebral blood volume; and can potentially reduce intracranial pressure, resulting in exceptional brain relaxation after dura opening. However, no study has examined continuous intravenous lidocaine infusion on brain relaxation, intraoperative opioid consumption and surgeon's satisfaction in adult patients undergoing craniotomy tumor removal. Methods: A total of 60 subjects scheduled for craniotomy tumor removal were enrolled in a double-blind, randomized controlled trial with consecutive sampling. Patients received either an intravenous bolus of lidocaine (2%) 1.5 mg/kg before induction followed by 2 mg/kg/h continuous infusion up to skin closure (lidocaine group) or placebo with similar volume (NaCl 0.9%). Neurosurgeons evaluated brain relaxation and surgeon's satisfaction with a 4-point scale, total intraoperative opioid consumption was recorded in μg and μg/kg/min. Results: All sixty subjects were included in the study. Lidocaine group showed better brain relaxation after dura opening (96.7% vs 70%; lidocaine vs placebo, P < .006), less intraoperative fentanyl consumption (369.2 μg vs 773.0 μg; P < .001, .0107 vs .0241 μg/kg/min; lidocaine vs placebo, P < .001). Higher surgeon's satisfaction was found in lidocaine group (96.7% vs 70%, P = .006). No side effects were observed during this study. Conclusions: Continuous lidocaine intravenous infusion improves brain relaxation after dura opening, and decreases intraoperative opioid consumption, with good surgeon satisfaction in adult patients undergoing craniotomy tumor removal.